Figuras galaicas del termalismo - Rodríguez Migues, Luis (Anales de Hidrología Médica, 2007)
With no intention to be exhaustive, but with vision and wit, we tried to recreate “the hidden history” of the main personalities in the scientific and business field of Termalism in Galicia throughout the past centuries. Both scientists and promoters have contributed to the development of the Spanish Medical Hydrology, and are presently waiting for followers of their labor to continue their work in order to achieve the place that Terminalism deserves in the 21th Century.